Konvergensi International Financial Reporting Standards (IFRS) Terhadap Manajemen Laba Di Indonesia : (Studi Konseptual) - Galih Suryo Linuhur (AKUNTANSI 45, 2023)
IAI (Indonesian Accounting Association) established financial accounting standards in Indonesia in 2012, namely PSAK which converges from IFRS (International Financial Reporting Standards). One of the aims of the adoption is to reduce the number of earnings management practices. Because earnings management does not show the facts of financial statements with the actual condition of the company. The purpose of this study is to dig deeper into the fact of the relationship between IFRS convergence and earnings management. The method used in this study is a literature study method with secondary data from literature related to IFRS convergence in earnings management, especially in Indonesia. The results of this study indicate that IFRS convergence and minimizing earnings management are not related to one another, it is IFRS convergence that causes earnings management practices.